The Champagne Tap: Time to Pop the Cork?. (20th April 2020) - Green, Rebecca S.; Cruz, Andrea T.; Freedman, Stephen B.; Fleming, Alesia H.; Balamuth, Fran; Pruitt, Christopher M.; Lyons, Todd W.; Okada, Pamela J.; Thompson, Amy D.; Mistry, Rakesh D.; Aronson, Paul L.; Nigrovic, Lise E.; et al.
Abstract: Background: A "champagne tap" is a lumbar puncture with no cerebrospinal fluid (CSF) red blood cells (RBCs). Clinicians disagree whether the absence of CSF white blood cells (WBCs) is also required. Aims: As supervising providers frequently reward trainees after a champagne tap, we investigated how varying the definition impacted the frequency of trainee accolades. Materials & Methods: We performed a secondary analysis of a retrospective cross‐sectional study of infants ≤60 days of age who had a CSF culture performed in the emergency department (ED) at one of 20 centers participating in a Pediatric Emergency Medicine Collaborative Research Committee (PEM CRC) endorsed study. Our primary outcomes were a champagne tap defined by either a CSF RBC count of 0 cells/mm 3 regardless of CSF WBC count or both CSF RBC and WBC counts of 0 cells/mm 3 . Results: Of the 23, 618 eligible encounters, 20, 358 (86.2%) had both a CSF RBC and WBC count obtained. Overall, 3, 147 (13.3%) had a CSF RBC count of 0 cells/mm 3 and 377 (1.6%) had both CSF WBC and RBC counts of 0 cells/mm 3 (relative rate 8.35, 95% confidence interval 7.51 to 9.27). Conclusions: In infants, a lumbar puncture with a CSF RBC count of 0 cells/mm 3 regardless of the CSF WBC count occurred eight‐times more frequently than one with both CSF WBC and RBC counts of 0 cells/mm 3 . A broader champagne tap definition would allow more frequent recognition of procedural success, with the potential to foster a supportive community during medical training, potentially protecting against burnout.